Development of learning modules with the concept of religious moderation to facilitate students' mathematical literacy skills - Mubarak, Ashar; Nur, Fitriani; Baharuddin, Baharuddin; Idris, Ridwan; Abrar, Andi Ika Prasasti (Indonesian Journal of Science and Mathematics Education, 2025)
Radicalism in religious life has become a serious problem, leading to the emergence of the term religious moderation in society. On the other hand, the low level of mathematical literacy in higher education also requires attention. This study aims to develop a learning module based on religious moderation to improve students' mathematical literacy. The module was developed using the ASSURE model. The validation results by experts showed a score of 3.814, categorized as "very valid." Through a lecturer questionnaire, the practicality test obtained a score of 3.56, which was categorized as "very positive," while the student response was 3.276, which was categorized as "good." The effectiveness of the module, reviewed from the results of the mathematical literacy test, showed that 50% of students were in the moderate category and 25% in the high category. Thus, this learning module is declared valid, practical, and effective. This study shows that integrating religious moderation values in mathematics learning improves students' cognitive abilities and forms a tolerant attitude and critical thinking, making a real contribution to the development of values-based mathematics education in higher education.